Integration of Artificial Intelligence in Learning: An Analysis of The Effectiveness of Chatbot Use on Student Independence - Erliza Septia Nagara; Esti Raihana; Bambang Amir Alhakim; Muhammad Arsyad; Muhammad Muhammad (Universitas Pahlawan Tuanku Tambusai, 2026)
The development of artificial intelligence (AI) technology has changed the paradigm of education globally, particularly through the use of interactive chatbots as a medium for independent learning. This study aims to analyze the effectiveness of using AI-based chatbots in improving student learning independence in higher education. The research method used is a quasi-experimental quantitative approach with a pretest-posttest control group design. The study sample included 180 students who were randomly divided into an experimental group (chatbot- assisted learning) and a control group (conventional learning). The data collection instrument used a Likert scale questionnaire that measured indicators of learning independence (initiative, goal setting, learning strategies, self-monitoring, and evaluation of results) as well as an academic ability test. Data analysis was carried out using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results of the analysis show that the use of AI chatbots has a positive and significant effect on student learning independence with a path coefficient () and contribution to learning achievement of 38.4% (Chatbots have proven effective as digital scaffolding, providing instant feedback and customizing materials to individual learning pace. The implications of this research underscore the importance of structured AI technology integration into higher education curricula to foster student autonomy and self-regulation in the digital age.